Perinatal outcomes following cell‐free DNA screening in >32 000 women: Clinical follow‐up data from a single tertiary center. (27th July 2018) - Liang, Dong; Lin, Ying; Qiao, Fengchang; Li, Hang; Wang, Yan; Zhang, Jingjing; Liu, An; Ji, Xiuqing; Ma, Dingyuan; Jiang, Tao; Hu, Ping; Xu, Zhengfeng
Abstract: Objective: Cell‐free DNA (cfDNA) screening for aneuploidy was clinically introduced in 2011. We aim to focus on the follow‐up information from a single tertiary center undergoing genome‐wide cfDNA screening to evaluate this technology. Method: A total of 32 431 cases were retrospectively reviewed. The screening was performed using a BGI protocol, and the cfDNA results were analyzed together with the pregnancy outcomes, confirmatory testing results, and ultrasound findings. Results: Of the 32 431 cfDNA screening cases, successful follow‐up was conducted in 287 (82.2%) cases with high‐risk cfDNA results, 85 (94.4%) cases with copy number variation (CNV) and rare autosomal trisomy (RAT) results, and 26 060 (81.5%) cases with low‐risk cfDNA results. Among them, 234 with high‐risk cfDNA results chose invasive testing, revealing 169 true positive cases. In cases with CNV and RAT results, 45 cases underwent invasive diagnosis, revealing six pathogenic CNVs and three uniparental disomies. In cases with low‐risk cfDNA results, three false negative cases were confirmed. Conclusion: Cell‐free DNA screening appears to be effective in detecting the common autosomal aneuploidies, but one‐third of our cohort with high‐risk results rejected confirmatory testing. Our data provide information on the clinical experience of large‐scale whole‐genome cfDNA screening that has global relevance for the implementation of this technology. Abstract : What's already known about this topic? Noninvasive prenatal screening based on cell‐free DNA (cfDNA) has become integrated into clinical practice for detection of common fetal chromosomal aneuploidies. In addition, genome‐wide cfDNA screening has also been available although its routine use is still controversial. However, comprehensive evaluation using large‐scale follow‐up information for cfDNA screening, especially for the low‐risk cases, is still limited. What does this study add? We report the detailed clinical follow‐up of 32 431 cfDNA screening cases performed in our tertiary center. In the group of women who received high‐risk cfDNA results but did not have confirmatory diagnostic testing, 23% proceeded directly to termination of pregnancy, 30% terminated due to ultrasound abnormalities, and 15% experienced an unintended pregnancy loss. In the group of 31 958 women who received low‐risk cfDNA results, 0.5% underwent diagnostic testing and three cases of false negative were confirmed. In the subgroup of 31 449 women who underwent genome‐wide cfDNA screening, 90 cases of copy number variations (CNVs) or rare autosomal trisomies (RATs) were detected and six pathogenic CNVs and three cases of uniparental disomy were confirmed.